Development of the KePO Information System as an Effort for Online Breast Cancer Early Detection - Novitarum, Lilis; Ginting, Arjuna; Sitepu, Aprilita Br (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
The primary cause of cancer-related deaths in women is breast cancer. While its best efforts, the Indonesian government has not been able to considerably lower the incidence of breast cancer while pushing for programs for clinical breast examinations (CBE) and breast self-examination (BSE). Less knowledge exists among reproductive women about early diagnosis of breast cancer symptoms. A lack of knowledge about breast cancer may have an impact on this. Reproductive Women can use the latest technological advancements as a tool to raise their self-awareness and prevent breast cancer. In an attempt to identify breast cancer early, this project attempts to create an online breast cancer prevention (KePO) information system. Through application architectural design and system development, this research creates a KePO information system. The team has created a website with the URL https://kepoinaja.my.id/ as part of an information system for breast cancer prevention. There is an article menu and consultation on this page. Reproductive women can use the consultation menu to find out their breast cancer risk score and the articles menu to read information about breast cancer. It is intended that by offering advice on how to prevent breast cancer risk factors, reproductive women through the KePO website can lower the incidence of breast cancer.